Pengaruh Kualitas Pelayanan,Komitmen Dan Disiplin Terhadap Motivasi Belajar Mahasiswa - Mardah, Siti; Harnida, Muthia; Santi, Apriya; Alfisah, Erni; Purboyo, Purboyo (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2023)
This research aims to measure the impact of service quality, commitment and discipline on the learning motivation of economics students at the Islamic University of Borneo MAB Banjarmasin. The test equipment used for this research uses the IBM version of SPSS 22. Normality Test and Termination Coefficient Test. The population was 275 students (7 classes) in semester 5 who took the cost management course. The sample was obtained as many as 163 people from the number of students who were used as the population. The number was obtained using the slovin formula. Through this research, it was partially concluded that the variables X1, X2 and X3 has a positive and significant effect on variable Y. Likewise, from the results of the simultaneous test, it can be concluded that the independent variables (X1.X2 and X3) have an effect on the variable Y (dependent).